Cryptography : the key to digital security, how it works, and why it matters - Martin, Keith M. (HighBridge Audio, 2020)
Despite its reputation as a language only of spies and hackers, cryptography plays a critical role in our everyday lives. Though often invisible, it underpins the security of our mobile phone calls, credit card payments, web searches, internet messaging, and cryptocurrencies-in short, everything we do online. Increasingly, it also runs in the background of our smart refrigerators, thermostats, electronic car keys, and even the cars themselves. As our daily devices get smarter, cyberspace-home to all the networks that connect them-grows. Broadly defined as a set of tools for establishing security in this expanding cyberspace, cryptography enables us to protect and share our information. Understanding the basics of cryptography is the key to recognizing the significance of the security technologies we encounter every day, which will then help us respond to them. What are the implications of connecting to an unprotected Wi-Fi network? Is it really so important to have different passwords for different accounts? Is it safe to submit sensitive personal information to a given app, or to convert money to bitcoin? In clear, concise writing, information security expert Keith Martin answers all these questions and more, revealing the many crucial ways we all depend on cryptographic technology.